On Two Projection Algorithms for the Multiple-Sets Split Feasibility Problem. (15th December 2013) - Dong, Qiao-Li; He, Songnian
Abstract : We present a projection algorithm which modifies the method proposed by Censor and Elfving (1994) and also introduce a self-adaptive algorithm for the multiple-sets split feasibility problem (MSFP). The global rates of convergence are firstly investigated and the sequences generated by two algorithms are proved to converge to a solution of the MSFP. The efficiency of the proposed algorithms is illustrated by some numerical tests.